Future Contracts and Delayed Contracts - Hussain Hadi Abdulameer (Technium Social Sciences Journal, 2024)
The contracts which are used by companies and investors to be careful of the risk or speculation of business are called future contracts & delayed contracts. Future & delayed contracts are considered as a good instance of etymological belongings that extract their values from the underlying belongings. A future contract is a unified legitimate deal to buy or sell something at a predetermined price and at a specific time in the future. The traded belonging is mostly a commodity or financial tool. The price which is pre-determined earlier and at which both parties are agreed upon (i.e. to buy and sell the belonging) is known as the delayed price. The specific time in the future is known as the delivery date which means when delivery and payment occur. The contracts which are negotiated on futures exchanges act as a market between buyers and sellers. The person who buys the contract is known as the holder of a long position and the person who sells the contract is known as the holder of the short position. A futures contract for stocks is a cash-settled future contract on the value of a particular stock market index. Future contracts for stocks are defined as one of the high-risk trading tools in the market. Future contracts for Stock market indicator are also used as indicators to determine market sentiment.